The role of the constitutional judge in safeguarding the right to health of persons deprived of liberty in the state of Nuevo León - Sánchez Hernández, Edgar (Revista Internacional & Comparada de Derechos Humanos, 2025)
Based on the constitutional and conventional framework, this study examines the role of the constitutional judge within the penitentiary context of the State of Nuevo León, taking into account the structural vulnerability faced by persons deprived of liberty, particularly with respect to their fundamental right to health. The analysis seeks to determine whether constitutional judicial action fulfills its protective function or, conversely, remains confined to a formalistic and restrictive approach that limits effective judicial protection. Finally, the study reflects on the need to strengthen the role of the constitutional judge as an agent of transformation and as a guarantor of the real and substantive protection of human rights.
Keywords: constitutional law; writ of amparo; penitentiary law